Sistema de captura de CO2 em caldeiras de biomassa para a produção de precipitado de carbonato de cálcio (PCC): Uma revisão sistemática e análise teórica - Saura, Marcelo (2025)
The growing concern with greenhouse gas emissions has driven research into viable technologies for capturing and utilizing these gases, particularly CO2. This work is structured into three chapters. The first presents a literature review of CO2 capture and reuse technologies, including absorption, adsorption, SARC, membranes, and oxycombustion, applied to thermal energy generation systems using renewable fuel sources. It emphasizes economic feasibility and carbon footprint reduction in PCC production for the paper industry. The second chapter covers a bibliometric and systematic review that helped identify scientific trends and technological advancements in CO2 capture, as well as evaluate the economic and operational feasibility of the SARC system for reducing carbon footprints in the industrial sector. A total of 6,228 documents were analyzed from the Web of Science platform (1997–2023), using the terms “CO2 capture,” “Captura de CO2,” “Flue gas,” and “Gases de combustão,” from which 362 articles were selected for systematic review. It was observed that 52.68% of global publications occurred between 2018 and 2023, while 43.03% of Brazilian studies were published between 2021 and 2023. The most relevant fields included engineering, fuels and energy, and chemistry, with emphasis on technologies such as chemical absorption, adsorption, membranes, oxy-combustion, and the SARC system, which stands out for its lower steam demand and ease of integration into existing industrial facilities. The third chapter presents a theoretical scenario for CO2 capture and utilization in the production of PCC in a pulp and paper mill, using the SARC system as the capture technology. For this, three operational PCC production scenarios were simulated using ASPEN Plus V.14 and Vulcano 2.5: current PCC production from non-renewable CO2 sources, PCC production using simulated data from CO₂ generation by a hypothetical biomass boiler without a capture system, and PCC production using CO2 captured by the SARC system. Although the capture system efficiency was initially estimated at 80%, bottlenecks in the PCC plant’s hydrators reduced this efficiency to 27.2%. Even so, the simulation predicts a theoretical daily PCC production increase from 301.4 to 701.4 tons, representing a 204% increase in contribution margin. Moreover, replacing cellulose with PCC in paper production demonstrated additional economic potential, estimated at approximately R$ 3.02 million per month for each 1% increase in PCC content, provided that paper quality is not compromised. These findings provide a foundation for developing more efficient and sustainable approaches in the industrial sector, although the observed limitations, especially those related to adsorbents highlight the need for further research.